A Jurisprudence of Doubt: Deliberative Autonomy and Abortion - Cohen, Jane Maslow (Columbia Journal of Gender and Law, 1992)
“Liberty finds no refuge in a jurisprudence of doubt.” With this stirring pronouncement, the decision of the Supreme Court in Planned Parenthood v. Casey begins. The tense wait that had preceded the Court’s decision had attained the quality of a death watch for Roe v. Wade. Both proponents and opponents of the abortion right had predicted that Casey would engender a categorical response to Roe, despite the fact that the Pennsylvania statute under review did not deal with abortion in prohibitive terms: either, it was supposed, Roe would be overruled-the more common prediction, given the Court’s most recent changes in membership-or, somehow, it would get reaffirmed. These dichotomous predictions failed, even as Casey’s opening rhetoric fails, to account for the new positions in abortion jurisprudence that the Court’s splintered decision making in the case denotes. While a fragile, five-member majority was able to preserve the “essential” holding of Roe v. Wade by affirming that states may not constitutionally prohibit abortion, Roe’s analytic structure, which had served as the bulwark against first- trimester regulation, was destroyed. At the same time, two separate coalitions of Justices, accounting for seven members of the Court, overcame their theoretical and strategic differences to join in upholding all but one of the abortion restrictions before them-restrictions whose prototypes had failed to pass constitutional muster in earlier attempts over the past decade. But the most striking feature of the Court’s latest abortion case may not be its hair-raising rescue of the abortion right, shorn naked of the protective analytic structure of Roe. Rather, the aspect of greatest continuing concern may be the attempt by the three Justices who authored Casey’s unusual joint opinion, to whom I shall refer as the O’Connor coalition, to maroon abortion jurisprudence on an island heaped with doubt: a new sense of doubt about the integrity of the abortion right; doubt about the extent of its constitutionally permissible regulation; and a revived form of doubt about women’s capacity to exercise autonomous judgment about the abortion decision-a doubt that has long functioned as a motivating force within our general culture and within the specific history of abortion law. In this Essay, I intend to explore this new jurisprudence of doubt and to defend the right to abortion against the troubling regulatory encroach- ment on women’s judgmental autonomy that the new jurisprudence portends. In so doing, I shall argue that the effect of this encroachment and the justifications offered to support it in Casey is to split the abortion right into two components: a strong, non-regulable right to decide to end a pregnancy by means of abortion, which I shall call the right to decisional autonomy, and a more feeble, highly regulable right to deliberate on each woman’s own terms about the decision to terminate her pregnancy, which I shall call the right of deliberative autonomy. It is the latter of these rights which now must weigh off, in some uneasy balance, against state efforts to influence a woman’s choice and to shape the environment of choice-efforts I shall refer to, in what follows, as deliberative intervention- ism. It is my intention to provide several bases for criticism of this dualistic approach to abortion regulation as well as reasons to be critical of various modes of deliberative interventionism. Toward the end of the Essay, I target the effects of my criticism on the coming development of doctrine.